The effect of feeding on CO2 production and energy expenditure in ponies measured by indirect calorimetry and the 13C-bicarbonate technique. (16th July 2015) - Jensen, R. B.; Kyrstein, T. D.; Junghans, P.; Tauson, A. H.
Abstract : Energy expenditure (EE) can be estimated based on respiratory gas exchange measurements, traditionally done in respiration chambers by indirect calorimetry (IC). However, the 13 C-bicarbonate technique ( 13 C-BT) might be an alternative minimal invasive method for estimation of CO2 production and EE in the field. In this study, four Shetland ponies were used to explore the effect of feeding on CO2 production and EE measured simultaneously by IC and 13 C-BT. The ponies were individually housed in respiration chambers and received either a single oral or intravenous (IV) bolus dose of 13 C-labelled sodium bicarbonate (NaH 13 CO3 ). The ponies were fed haylage 3 h before ( T −3 ), simultaneously with ( T 0 ) or 3 h after ( T +3 ) administration of 13 C-bicarbonate. The CO2 produced and O2 consumed by the ponies were measured for 6 h with both administration routes of 13 C-bicarbonate at the three different feeding times. Feeding time affected the CO2 production ( P <0.001) and O2 consumption ( P <0.001), but not the respiratory quotient (RQ) measured by IC. The recovery factor (RF) of 13 C in breath CO2 was affected by feeding time ( P <0.01) and three different RF were used in the calculation of CO2 production measured by 13 C-BT. An average RQ was used for the calculations of EE. There was no difference between IC and 13 C-BT for estimation of CO2 production. An effect of feeding time ( P <0.001) on the estimated EE was found, with higher EE when feed was offered ( T 0 and T +3 ) compared with when no feed was available ( T −3 ) during measurements. In conclusion, this study showed that feeding time affects the RF and measurements of CO2 production and EE. This should be considered when the 13 C-BT is used in the field. IV administration of 13 C-bicarbonate is recommended in future studies with horses to avoid complex 13 C enrichment-time curves with maxima and shoulders as observed in several experiments with oral administration of 13 C-bicarbonate.